PENINGKATAN EFISIENSI PENGGUNAAN ENERGI LISTRIK UNTUK PENCAHAYAAN DI RUANG LABORATORIUM LISTRIK DENGAN LHE - , Eko Widiarto, Eka Firmansyah, ST. M.Eng., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The purpose of energy safe lamps (ESL) on a building is to provide artificial lighting during the day and night. Aside from that it is important to maintain energy efficiency due to economic and environmental aspect during the application of the ESL. The research discusses the improvement of the efficiency of electric energy consumption which was obtained from the substitution of V shaped luminary with ESL. The research was initiated by measuring the existing condition, measuring the lighting level in a laboratory, testing the performance of one sample of V shaped luminary, and the testing of ESL performance (using 5 different brands). Then, a design of a lighting system using the most efficient ESL was applied in the given laboratory. The research showed that power consumption reduced from 3136 W to 668 W when the ESL was used. Therefore, there was a saving of 2468 W or 79%. In the case of the consumption of electrical energy, there was a reduction from 4,892.28 KWh to 1,043 KWh when the ESL was used. Therefore, there was a saving of 3849 KWh or 79%. There was also a reduction of CO2 emission of 2.77 T CO2